Against problem solving by segment method - Castellini, Antonella (EDiMaST: Experiences of Teaching with Mathematics, Sciences and Technology, 2016)
The segment methods as graphic-methods for problem solving, are one of the crucial points in Italian lower secondary school. Usually, they are faced during grade 6 in Problem Solving classes. However, the conceptual gap that has to be faced is not problem solving but the conversion from one representational register to another. Pupil’s difficulties could be overcome using other representations and they requires a specific preliminary work of conversion between many different representational registers. In this paper some activities aimed to overcome this gap are presented. Such activities are suitable for a conscious and significant introduction to algebraic language.